The Effect of Knowledge Level on Anemia among Adolescent Girls in Coastal West Lombok - Rachman, Amanda Azkiyah; Lestarini, Ima Arum; Bahraen, Raehanul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Hemoglobin levels below 12 g/dL, or anemia, continue to be a serious health issue in developing nations like Indonesia. Teenage girls in coastal areas are particularly at risk. Although research in West Lombok is still in its infancy, knowledge is thought to be the first step in prevention. The aim of this study is to analyze the effect of knowledge level on anemia among adolescent girls in coastal West Lombok. This categorical analytic observational study applied a cross-sectional design, chosen for its efficiency in assessing associations at a single point in time. Purposive sampling recruited 101 respondents who met inclusion criteria (female, aged 15–19, residing in coastal West Lombok, willing to participate). Exclusion criteria included chronic illness or refusal of blood testing. Data were obtained using a validated online questionnaire and hemoglobin measurement. Statistical analysis employed Chi-square test with SPSS version 25.0. The result indicated no significant association was found between knowledge and anemia (p=0.599). However, girls with low knowledge had 1.3 times higher risk of anemia (OR=1.295; 95% CI: 0.493–3.399), suggesting other contributing factors such as nutrition and socioeconomic conditions. In conclusion, knowledge alone does not significantly affect anemia incidence. Integrated education, nutritional interventions, and routine iron supplementation are recommended, with further studies needed.